Comparative evaluation of the force required to fracture coronal segments reattached using different methods. Issue 2 (22nd December 2021) - Sreen, Deepti; Abraham, Dax; Gupta, Alpa; Singh, Arundeep; Aggarwal, Vivek; Chauhan, Nishant; Jala, Sucheta; Mehta, Namrata
Abstract: Background/Aim: Anterior teeth are prone to traumatic injuries. Their management is necessary in order to maintain the pulp and esthetics. Various methods have been reported for fragment reattachment of fractured teeth but there is no consensus on which is the best technique. The aim of this study was to compare the force required to fracture reattached fragments using polyethylene fibers in vertical grooves on the external surface of teeth, fiber‐reinforced composite post and circumferential chamfer. Material and Methods: Forty‐eight extracted maxillary central incisors were sectioned using a disk and randomly divided into 4 groups ( n = 12): Group 1: control group, Group 2: reattachment followed by placement of two external vertical grooves on the labial surface and restored with polyethylene fibers and hybrid composite, Group 3: reattachment followed by two external vertical grooves and filled with fiber posts and composite, and Group 4: reattachment followed by circumferential chamfer at the fracture line and restored with composite. The forces required to fracture the reattached fragments were measured using a Universal testing machine. Data were analyzed using the Kruskal–Wallis test. Pairwise multiple comparison procedure was done using the Student–Newman–Keuls Method. Results: The highest values for force required to fracture were observed in the fiber post group and the lowest in the Ribbond group ( p < .05). The fiber post group had significantly different results compared to the Ribbond and Chamfer preparation groups ( p < .05). However, the difference of rank between the fiber post and control groups was not significantly different ( p > .05). Conclusion: The force required to fracture the fiber post group was closest to that of intact teeth followed by the chamfer and Ribbond groups, respectively.